Short term outcome of epileptic Seizure in children attending at Paediatric Neuroscience Department of Dhaka Shishu Hospital - Quaderi, Humaira Rafiqa; Sarker, Shaoli; Kanta, Shayla Imam; Yasmeen, BH Nazma (Northern International Medical College Journal, 2020)
Background : The optimal response to antiepileptic treatment is the control of seizures. In different studies, it has been shown that childhood epilepsy presents with a variable course, and approximately one-third of epilepsy experience alternating relapse and remission. Some of them do not become seizure-free, despite adequate treatment. Objectives : This study aimed to see the short-term outcome of seizures in children with epilepsy (whether the seizure is controlled or not) and to correlate them with different predictors like socio-demographic factors, associated comorbidities, and adherence with antiepileptic drugs. Methods : This retrospective observational study was conducted in an Epilepsy Clinic of Paediatric Neuroscience Department of Dhaka Shishu Hospital (DSH) over a period of 3 years from January 2013 to December 2015. During this period 1-year follow-up record of each patient was analyzed. Information on bio demographic data, clinical and developmental assessment done by a multidisciplinary team was analyzed. Results : A total of 100 children who had epilepsy were included in this study. Unfavorable outcome (uncontrolled seizure) was found in children <5 years of age, children from the rural area, and those whose parents education were below secondary level (p values were 0.05, 0.03 and 0.04 respectively). Also, the unfavorable outcome was found in children who had H/O perinatal asphyxia (PNA), motor problem, and feeding problem (p-value=0.5, 0.002, 0.05 respectively). After 1 year of regular follow up milestone of development was improved in more than one 1domain in 51children. But there was no improvement found or their condition remained unchanged in 49 children. Northern International Medical College Journal Vol. 11 No. 1 July 2019, Page 411-414